2009
DOI: 10.1177/105268460901900303
|View full text |Cite
|
Sign up to set email alerts
|

“Where I came from, Where I am Now, and Where I'd like to Be”: Aspiring Administrators Reflect on Issues Related to Equity, Diversity, and Social Justice

Abstract: This study explores student reflections about issues related to equity, diversity, and social justice from an educational foundations course. Online reflections and course assignments were analyzed from 15 aspiring administrators for patterns. Findings indicate that (1) students were willing to engage and reflect on their experiences and cultural identity, (2) students used their worldviews as filters for these experiences, (3) students were not necessarily willing to experience discomfort for the sake of lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Indeed, scholarship on social justice had been plentiful among educational administration scholars in the years leading up to the ELCC update (e.g., Alemán, 2009; Alston, 2005; Bogotch, 2002; Brooks et al, 2007; K. M. Brown, 2004, 2006; Hernandez & Marshall, 2009; Jean-Marie, Normore, & Brooks, 2009; Lugg & Shoho, 2006; Marshall & Ward, 2004; McKenzie, Skrla, & Scheurich, 2006; McKinney & Capper, 2010; Murtadha & Watts, 2005; Pounder, Reitzug, & Young, 2002; Shields, 2004; Skrla, Scheurich, Johnson, & Koschoreck, 2001). While there are a range of contemporary examples, we find Theoharis’ (2007) definition of social justice leadership to be more relevant, up-to-date, direct, and useful than that cited by the ELCC report.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, scholarship on social justice had been plentiful among educational administration scholars in the years leading up to the ELCC update (e.g., Alemán, 2009; Alston, 2005; Bogotch, 2002; Brooks et al, 2007; K. M. Brown, 2004, 2006; Hernandez & Marshall, 2009; Jean-Marie, Normore, & Brooks, 2009; Lugg & Shoho, 2006; Marshall & Ward, 2004; McKenzie, Skrla, & Scheurich, 2006; McKinney & Capper, 2010; Murtadha & Watts, 2005; Pounder, Reitzug, & Young, 2002; Shields, 2004; Skrla, Scheurich, Johnson, & Koschoreck, 2001). While there are a range of contemporary examples, we find Theoharis’ (2007) definition of social justice leadership to be more relevant, up-to-date, direct, and useful than that cited by the ELCC report.…”
Section: Resultsmentioning
confidence: 99%
“…She notes that intentionally engaging in the steps or reflecting and then writing can help principals become reflective practitioners. Hernandez and Marshall (2009) studied 15 educational leadership students' online reflections about issues related to equity, diversity, and social justice and found that preparation programs can play a large role in helping students explore their cultural identities. More recently and specific to social justice, Marshall and Hernandez (2013) analyzed the written reflections of aspiring principals in two principal preparation courses that purposely examined the social justice leader's role in addressing sexual orientation issues in schools.…”
Section: Toward Using Racial Reflection As a Pedagogical Toolmentioning
confidence: 99%
“…This suggests that finding potential social justice-minded leaders may be difficult. Likewise, Hernandez and Marshall (2009) found that while all of their leadership candidates expressed interest in reflecting about topics related to equity, diversity, and social justice, only a few leadership candidates were actually willing to experience the discomfort of placing themselves in new cultural contexts and reflecting on their own tendencies toward ethnocentric assumptions about what is "universal" as well as how they benefit from White privilege. Theoharis (2007) identified key practices within the process of enacting social justice.…”
Section: Leadership For Social Justicementioning
confidence: 99%
“…Theoharis (2007) notes that while theoretical work has been advanced in the area of SJL, a gap remains for examinations of SJL in practice. Similarly, Hernandez and Marshall (2009) suggest that much work remains to be done in preparing school leaders to transform schools so that all students succeed. Just as Jean-Marie, Normore, and Brooks (2009) suggest, "in order to move beyond high-sounding abstractions and turn to research and action" (p. 19) we examine how one principal faced the challenges in transforming his school.…”
Section: Leadership For Social Justicementioning
confidence: 99%